2021
DOI: 10.1177/14799731211002240
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of potential respiratory symptoms in survivors of hospital admission after coronavirus disease 2019 (COVID-19): A systematic review and meta-analysis

Abstract: Knowledge on the sequelae of Coronavirus Disease 2019 (COVID-19) remains limited due to the relatively recent onset of this pathology. However, the literature on other types of coronavirus infections prior to COVID-19 reports that patients may experience persistent symptoms after discharge. To determine the prevalence of respiratory symptoms in survivors of hospital admission after COVID-19 infection. A living systematic review of five databases was performed in order to identify studies which reported the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
134
1
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 46 publications
10
134
1
11
Order By: Relevance
“…Another systematic review have reported that main post-COVID-19 sequelae were post-infectious fatigue, persistent reduced lung function and carditis; however, this review did not pooled data on post-COVID symptoms since it focused on functional impairments [49] . Another meta-analysis reported that the most common respiratory post-COVID-19 symptoms reported by hospitalized COVID-19 survivors included fatigue, dyspnoea, chest pain, and cough showing prevalence rates of 52%, 37%, 16% and 14%, respectively between 3 weeks and 3 months after hospital discharge [50] . These prevalence data are similar to our pooled data observed at 60days follow-up; however, Cares-Marambio et al [50] pooled studies without distinction on follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review have reported that main post-COVID-19 sequelae were post-infectious fatigue, persistent reduced lung function and carditis; however, this review did not pooled data on post-COVID symptoms since it focused on functional impairments [49] . Another meta-analysis reported that the most common respiratory post-COVID-19 symptoms reported by hospitalized COVID-19 survivors included fatigue, dyspnoea, chest pain, and cough showing prevalence rates of 52%, 37%, 16% and 14%, respectively between 3 weeks and 3 months after hospital discharge [50] . These prevalence data are similar to our pooled data observed at 60days follow-up; however, Cares-Marambio et al [50] pooled studies without distinction on follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis reported that the most common respiratory post-COVID-19 symptoms reported by hospitalized COVID-19 survivors included fatigue, dyspnoea, chest pain, and cough showing prevalence rates of 52%, 37%, 16% and 14%, respectively between 3 weeks and 3 months after hospital discharge [50] . These prevalence data are similar to our pooled data observed at 60days follow-up; however, Cares-Marambio et al [50] pooled studies without distinction on follow-up periods. Our systematic review/meta-analysis examined the prevalence of post-COVID-19 symptoms considering if patients were hospitalized or not and also separated by follow-up periods.…”
Section: Discussionmentioning
confidence: 99%
“…While the actual definition is lacking, a review identified that the most frequent symptoms of long COVID are fatigue and dyspnoea (i.e. shortness of breath) [ 17 , 18 ]. Other less typical symptoms include cognitive and mental disorders, headache, myalgia, chest and joint pains, smell and taste dysfunctions, cough, hair loss, insomnia, wheezing, rhinorrhea, sputum, and cardiac and gastrointestinal issues.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst most survivors will have a full recovery, short-term follow-up reveals that a high proportion of individuals still report fatigue or muscle weakness, dyspnea, joint pain, chest pain, and psychological symptoms, leading to impaired health-related quality of life [5,7,8,10]. Even individuals attending emergency departments but not admitted to hospital report a prolonged and debilitating set of symptoms after their acute episode, sometimes labelled as "long COVID" [9,12]-the growing recognition of which in the literature has given rise to the new concept of "post-acute COVID-19 syndrome" (PCS) [13].…”
Section: Introductionmentioning
confidence: 99%